Coil-assisted retrograde transvenous obliteration for managing complex gastric variceal bleeding: a pediatric case report and review of techniques - Hosseini, Amirhossein; Kiani, Iman; Khalili, Mitra; Alibeik, Mina; Khameneh Bagheri, Arash (Frontiers in Pediatrics, 2025)
IntroductionGastric variceal bleeding is a life-threatening complication of portal hypertension, associated with high morbidity and mortality. While conventional treatments such as endoscopic interventions, pharmacological therapy, and transjugular intrahepatic portosystemic shunt (TIPS) are standard, alternative approaches are needed for high-risk or anatomically complex cases. Coil-Assisted Retrograde Transvenous Obliteration (CARTO) has emerged as a promising technique, combining mechanical and chemical approaches to achieve durable hemostasis.Case presentationA 10-year-old girl with a history of congenital spherocytosis and splenectomy presented with hematemesis and a hemoglobin level of 4.4 mg/dl. Initial endoscopy revealed no esophageal varices, but gastric visualization was inconclusive due to active bleeding. CT angiography demonstrated extensive gastric fundal varices, confirmed by transhepatic portography. Management involved CARTO, utilizing sodium tetradecyl sulfate sclerotherapy and coil embolization. Post-procedure imaging showed successful obliteration of varices, and the patient's hemoglobin levels normalized. Follow-up at six months revealed complete symptom resolution.DiscussionCARTO offers a viable alternative for managing gastric varices in complex cases, particularly when TIPS or BRTO are unsuitable. Compared to BRTO, CARTO is less time-consuming and avoids large sheaths, reducing procedural risks. However, it is technically demanding and cost-intensive, requiring careful patient selection. This case demonstrates CARTO’s effectiveness in achieving hemostasis and managing challenging variceal anatomies.ConclusionCARTO is an effective option for managing high-risk gastric varices. Future studies should refine procedural techniques, improve patient selection, and explore advanced embolization materials to optimize outcomes.